Pengembangan Chatbot AI Untuk Pusat Pembelajaran Keluarga Sejahtera (PUSPAGATRA) Menggunakan Algoritma Naive Bayes - syahutama, ilham husada (JATISI, 2025)
The development of artificial intelligence (AI) technology has opened new opportunities to improve the efficiency of public services. This research develops an AI-based chatbot applied to the Family Welfare Learning Center (PUSPAGATRA) services at the Department of Population Control, Family Planning, Women's Empowerment, and Child Protection (Dinas PPKB PPPA) of Sragen Regency. Using the Naive Bayes algorithm, this chatbot is designed to provide information and guidance on family, health, women's empowerment, and child protection programs quickly and efficiently. This study shows that AI-based chatbots can answer various public inquiries accurately and relevantly. This implementation is expected to accelerate information access and improve the efficiency of public services in Sragen Regency. Keywords— AI, Chatbot, Naive Bayes, PUSPAGATRA, Public Service